Factors Inhibiting Teachers’ Curriculum delivery in Rural Secondary Schools of Namibia - Haufiku, Isidor; Mukenegeli, Elizabeth.Naitha.; Nakambale, Immanuel Nghitotelwa (Papanda Publisher, 2026)
The persistent decline in teachers' performance within the Shambyu Circuit has raised significant concerns, necessitating an investigation into the factors inhibiting effective curriculum delivery. This study examined the challenges affecting teachers' instructional practices in the Shambyu Circuit, Kavango-East Region, Namibia. A convergent parallel mixed-method research design was employed, integrating both quantitative and qualitative approaches. Data were collected through a survey questionnaire and focus group discussions. Quantitative data were analyzed using descriptive statistical methods, while qualitative data underwent thematic analysis. The findings revealed that several factors hinder effective curriculum delivery at the school level, including inadequate teaching and learning resources, poor infrastructure, ineffective leadership styles among school administrators, and low levels of teacher motivation. Furthermore, teacher-related factors such as deficiencies in pedagogical skills, professional communication, creativity, subject knowledge, and technological integration were identified as significant impediments to effective teaching. Additionally, the study established that teachers in the circuit lack access to continuous professional development (CPD) programs, further exacerbating these challenges. Based on these findings, the study recommends that the Ministry of Education, Arts, and Culture allocate adequate teaching and learning resources to schools to enhance instructional quality. Furthermore, regular leadership development programs should be implemented for school administrators, while ongoing professional development workshops should be provided for teachers to strengthen their pedagogical competencies and subject expertise.